1981
DOI: 10.1029/jc086ic06p05347
|View full text |Cite
|
Sign up to set email alerts
|

Forest vegetation as a sink for atmospheric particulates: Quantitative studies in rain and dry deposition

Abstract: Radionuclides in the atmosphere are associated with nonradioactive air particulates and hence serve to trace the fluxes of air particulates to various surfaces. Natural and artificial radioactivities found in the atmosphere have been measured in vegetation for 10 years to elucidate some of the mechanisms of acquirement by forest trees of atmospheric particulates. Whole tree analysis, in conjunction with soil assay, has served to establish the fraction of the flux of radionuclides retained by above-ground tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Thus, the bulk precipitation/throughfall ratio obtained here could be interpreted as a mere indication of matter being brought to foliar surfaces by rain, rather than the efficiency with which the Sitka spruce needles capture and retain the 210 Pb-carrier aerosols from bulk precipitation. Previous investigations by Russell et al (1981) have revealed high contamination surface densities of radioactive aerosols ( 7 Be, 144 Ce, 141 Ce and 95 Zr) on twig and limb surfaces of pine, oak and maple trees.…”
Section: Concentrations Of 210 Pb Aerosols In Rain and Throughfall Samentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, the bulk precipitation/throughfall ratio obtained here could be interpreted as a mere indication of matter being brought to foliar surfaces by rain, rather than the efficiency with which the Sitka spruce needles capture and retain the 210 Pb-carrier aerosols from bulk precipitation. Previous investigations by Russell et al (1981) have revealed high contamination surface densities of radioactive aerosols ( 7 Be, 144 Ce, 141 Ce and 95 Zr) on twig and limb surfaces of pine, oak and maple trees.…”
Section: Concentrations Of 210 Pb Aerosols In Rain and Throughfall Samentioning
confidence: 98%
“…The interaction of atmospheric radionuclides with forest soils is mainly due to the eluded or eroded aerosol laden radionuclides that had deposited onto plant foliage. The aspect of radionuclide accumulation by plant has been reviewed (Russell 1965;Russell et al 1981). The isotope of 210 Pb in the atmosphere has been shown to be particularly useful as an atmospheric tracer because it is associated mainly with submicronsized aerosols, which contain the bulk of the pollutant sulphur and nitrogen .…”
Section: Introductionmentioning
confidence: 99%
“…Given the limited penetration of 7 Be in the O horizon, the strong partitioning of Pb to organic matter (Kerndorff and Schnitzer, 1980;Sauve et al, 2000), the importance of dry deposition for atmospheric Pb (Miller and Friedland, 1994) and the long residence time of atmospheric Pb reported for O horizons (Wang and Benoit, 1997;Kaste et al, 2003Kaste et al, , 2006aKlaminder et al, 2006), it is unlikely that Pb is transported to significant depths in the soil following deposition. It is more likely that Pb is bound strongly to the initial surfaces that it comes into contact with, that is, live leaves and surface litter (Russell et al, 1981). As leaves containing Pb are buried by subsequent years of litterfall, Pb is quantitatively retained by the material.…”
Section: Processes Controlling the Vertical Distribution Of 210 Pb Exmentioning
confidence: 99%
“…Similar to Pb, these atoms hydrolyze even in acidic soils and thus strongly adsorb to mineral or organic phases (Kim et al, 1997;Artinger et al, 2002). Because the input functions for gasoline-derived Pb and the weapons fallout can be treated essentially as single short-duration events, and the atoms are sequestered by forest vegetation (Russell et al, 1981), the distributions are similar in the soil profiles: a contaminated layer at depth is overlain by fresh "clean" litter, and underlain by even older material that pre-dates the era of peak atmospheric contamination. However, pollutant Pb and weapons-derived nuclides were introduced into the atmosphere over different time intervals, and thus provide independent constraints of forest litter "exposure" age.…”
Section: Weapons-derived Falloutmentioning
confidence: 99%
“…Qualls et al (1991) found that up to 40% of freshly fallen leaf litter was extractable in water. Since the forest canopy scavenges significant amounts of aerosols from the troposphere (Russell et al, 1981) and the Oi layer scavenges metals from throughfall solutions, litter could be a source of mobile organic-Pb complexes. Tam et al (1991) found that approximately 10% of the total Pb in a litter layer was removed by a single water extraction (passing through a 2.5-µ m filter).…”
Section: Introductionmentioning
confidence: 99%